Directors’ Remuneration and Firm’s Performance : A Study on Malaysian Listed Firm under Consumer Product Industry - Mohd Waliuddin, Mohd Razali; Ng, Sue Yee; Hwang, Josephine Yau Tan; Akmal Hisham, Tak; Norlina, Kadir (Canadian Center of Science and Education, 2018)
Remuneration is broadly used as an incentive that affects decisions made and strategies planned by directors which cause great impact on firm performance and profitability. This study aims to investigate the directors’ remuneration of the consumer products sector focusing particularly on Malaysian listed companies under Consumer Product Industry. These firm’s performances are measured by return on assets (ROA) and return on equities (ROE). This study consists a sample of 40 Malaysian listed companies for the period of 2012 to 2014. After controlling for board size, CEO duality, firm size, firm age, and leverage; the regression results show director remuneration has positive relationship with firm performance (measured by ROA and ROE). This suggests that high remuneration is able to motivate and retain directors in order to perform their duty and work harder for the best interest of shareholders. The result also shows all variables affect firm performance differently.For future research, we recommend that this study be expanded using more samples from other industries and other measurement of firm performances such as growth and ratings.